PGMweb: an online tool for visualizing the X-ray beam path through plane grating monochromators - Patrick Yuheng Wang; Murilo Bazan da Silva; Matthew Hand; Hongchang Wang; Peter Chang; Victoria Beilsten-Edmands; Timur K. Kim; Tien-Lin Lee; Kawal Sawhney; Andrew C. Walters (Journal of Synchrotron Radiation)
We present here a newly developed software tool (called PGMweb) for computing and simulating the X-ray beam path through a plane grating monochromator (PGM), a key component in soft X-ray beamlines at modern synchrotron and free-electron laser facilities. A historical overview of the development of PGMs is presented, with special attention dedicated to the collimated PGM optical scheme found at several X-ray facilities worldwide. The analytical expressions that fully describe the geometry of a PGM are derived and have been implemented as functions in a Python library (pyplanemono). PGMweb is distributed as a web-based application that can be run in any modern browser without installation, making its use very straightforward for X-ray beamline designers and beamline scientists alike.